Sifat Optis Aktif Air dalam Medan Magnet pada Frekuensi Resonansi 50Hz-60Hz - Firdausi, K. Sofjan; Lego, Dro Dwi; Sugito, Heri (BERKALA FISIKA, 2007)
The interaction between external magnetic field modulated at 50-60 Hz and the dipoles of the sample induced by laser light modulated at 50-100 Hz has been studied. The magnetic field has the maximum value of 170 mT produced by a coil of 810 in turns. The source of light of 632,8 nm and 532 nm is modulated at the resonance value between 30 Hz and 100 Hz. The optical characteristic behavior studied in this research is the change of polarization E-direction of laser light in the aquades samples against the influence of external magnetic field. The result of experiment indicates that the change of laser polarization angle is linearly proportional with the increaseasing of modulated frequency and external magnetic field in sample materials. It is shown that the change of glycerine concentration changes also linearly direction of polarization. The verdet constants measured in the experiment for 632 nm and for 532 nm equal to (0,026 Â± 0,005) V (min/g-cm) and (0,025 Â± 0,003) V (min/g-cm), respectively. Key words: change of polarization, external magnetic fields, resonance frequency